Persecution, International Refugee Law and Refugees: A Feminist Approach - Crepin, Mathilde (Law and Migration, 2021)
This book explores the ambit of the notion of persecution in international law and its relevance in the current geopolitical context, more specifically for refugee women. The work analyses different models for interpreting the notion of persecution in international refugee law through a comparative lens. In particular, a feminist approach to refugee law is adopted to determine to what extent the notion of persecution can apply to gender-related forms of violence and what the challenges are in doing so. It proposes an interpretive model that would encourage decision makers to interpret the notion of persecution in a manner that is sufficiently protective and relevant to the profiles of refugees in the 21st century, most particularly to refugee women. The book will be of interest to academics and students in the field of public international law, international human rights law, international humanitarian law, immigration law, European law and refugee law, as well as those working in the areas of international relations.